PREFERENSI KESALEHAN WANITA DALAM FILM RELIGI (STUDI ANALISA FRAMING TERHADAP FILM KHALIFAH KARYA NURMAN HAKIM) - Sa`idah, Zahrotus (representamen, 2019)
â€œKhalifahâ€ is one of Nurman Hakimâ€™s movies that tells about conflict felt by the main figure on understanding Islam and the essence of wearing veil for Muslim after several bombing accidents in Indonesia. This movie had attracted many responses, pros and conts in term of how Hakim presents womenâ€™s veil and how he frames the suicide bombing tragedy conducted by terrorists. That is because this movie does not only deliver social reality of womenâ€™s veil but it is also demanded to deliver this reality neutrally. This article uses qualitative method and sociological communicative approach in order to seek womenâ€™s preferences on expressing their peities. It is found from this article that this movie attempts to neutralize the image of womenâ€™s veil in several scenes. Hakim also attempts to capture some bombing tragedies done by terrorists in Indonesia from two figuresâ€™ perspectives, namely Khalifah and Rasyid. In the end of the movie, the audiences have been challenged to choose between wearing veil or preserving morals.Keywords: Movie, Piety, Veil.